How Do CEO Values Influence IPO Speed? A Conceptual Analysis from the Upper Echelons Perspective. Issue 1 (June 2020) - Talaulicar, Till
The present article addresses the important, but widely neglected subject of initial public offering (IPO) speed that indicates how rapidly a firm develops from its foundation to be publicly listed. We argue that the time that elapses between start-up and going public depends on characteristics of the CEO who tends to largely influence the timing of the IPO decision. Based on conceptual analyses that combine upper echelons theory and the five-factor model of personality traits, we reveal a complex set of propositions about the direct effects of certain CEO values on IPO speed as well as about CEO- and firm-related variables that moderate these relationships. More specifically, we propose that the degrees of the CEO's emotional stability, extraversion, openness to experience as well as risk propensity tend to be positively associated with IPO speed, whereas the CEO's agreeableness and conscientiousness tend to decelerate the pace of going public. These effects tend to be stronger when the CEO is the founder of the firm, holds also the position of a chairperson (CEO duality) and/or owns substantial stakes of the company's equity. Firm size and the size of the top management team tend to weaken these direct relationships.